Application of magnetic and accelerometer sensors for the analysis of alpine ski peformance - Tsunoda, K.; Sasaki, T.; Hoshino, H. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
In alpine skiing, the direction and speed of a skier changes greatly with passing through gates. During turning, various forces (for example gravity, centrifugal force and friction) act on a skier. In the dynamics of alpine skiing, it is important to measure the forces acting on a skier. An accelerometer sensor has the advantage to be able to measure the force directly. To measuring the forces during ski race is useful for coaching. The purpose of this study is development of an analysis system for alpine skiing.